Ticks’ tricks: immunomodulatory effects of ixodid tick saliva at the cutaneous tick-host interface - Kleissl, Lisa; Weninger, Sophie; Winkler, Florian; Ruivo, Margarida; Wijnveld, Michiel; Strobl, Johanna (Frontiers in Immunology, 2025)
Due to changes in global climate, the geographic distribution of ticks and tick-borne infections is increasing and represents a growing global health concern for humans. Ticks of the genus Ixodidae are globally abundant and transmit a wide variety of pathogens that cause human infections, including tick-borne encephalitis and Lyme borreliosis. The transmission of pathogens into human skin while blood feeding causes changes in the local immune cell network and has various effects on structural skin cells, including sensory neurons. Recent studies have focused on the effect of tick saliva on cells at the cutaneous tick-host interface and have suggested a strong immunomodulatory function. Within seconds after a tick bite, saliva containing various bioactive molecules is secreted into the host’s skin, leading to vasodilation, inhibition of coagulation and anti-inflammatory actions. Inhibition of immune cell recruitment and cytokine secretion, facilitate prolonged tick attachment and blood feeding as well as pathogen transmission. Therefore, in recent years, efforts have intensified to identify tick salivary compounds by multi-omics approaches and investigate their individual effects on innate and adaptive immunological mechanisms. In this review, we summarize important features of tick saliva molecules and how they influence and modulate skin cell behavior on the tick-host interface to facilitate tick attachment and pathogen transmission. Further, we highlight immunomodulatory mechanisms of salivary compounds and their potential role as novel treatment agents for inflammatory skin diseases and in tick vaccine development.